INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE SYSTEM OF EDUCATION IN PHYSICS - STERBAKOVA, Katarina; SEBEN, Vladimir (Trends in education, 2008)
In the article, the author deals in brief with information and communication technologies and their place in teaching of Physics and in after school activities. She mentions their importance in an individual work of a student. She applies herself in brief to results of the project KEGA thanks to which chosen schools will obtain created methodical multimedia materials for teaching of Physics and for after school activities.
Keywords: IKT. Multimedia. Internet. Physics. After school activities.